Academic writing - Strongman, Luke (Cambridge Scholars, 2013)
How do I improve my essay writing skills? Where can I learn quickly how to improve my speech writing? How does writing for the web differ from conventional writing? Are there some categories of mistakes that people commonly make in attempting to write good prose? How can I be persuasive in my writing style? How did language evolve? What is 'genre theory'? How do I become creative in my prose writing? These and other curious and relevant questions are answered in Academic Writing. Writing is a ...